Mutual insurance risks - L. A. Orlanyuk–Malitskaya (Путеводитель предпринимателя)
The article considers the risk status of mutual insurance organizations. The growing popularity of mutual insurance among representatives of the field of material production, carriers, tourism business and other market participants, on the one hand, and the widespread opinion about the increased stability of the activities of a mutual insurance organization, on the other hand, sets the task of determining the risk status of a mutual insurance company, which will make it possible to formulate the main directions of risk–oriented regulation of such organizations. According to the author, the mutual insurance organization is subject to a significant number of various risks of risks, both event and economic and social. It is suggested that at least the following risk groups are inherent in a mutual insurance organization: risks due to the nature of insurance; risks arising from reciprocity as a technology; market risks of the mutual insurance organization; risks of an individual participant in mutual insurance in the part affecting the interests of the functioning of mutual insurance. Analysis of these risk groups makes it possible to come to the conclusion that the risk management of mutual insurance organizations should be built differently for organizations uniting individuals or large legal entities. For mutual companies of individuals, it is necessary to provide for built–in risk management mechanisms; for mutual societies that unite legal entities, risk management should be systemic and combine both the risks of the organization and its participants (enterprises).